Cubosomes: A Potential Drug Delivery System - Chaudhary, Kajal; Sharma, Devender (Asian Journal of Pharmaceutical Research and Development, 2021)
The discovery of cubosomes is a classic story and deals with food science, differential geometry, biological membranes and digestive processes. Cubosomes are highly balanced and nanoparticles in design formed primarily from the lipid cubic state and protected by a polymer-based outer circle. Hydrating a surfactant that designates cubic phase and then disperses a solid state into smaller particles, typically forms cubosomes. They behave concretely like rheology with unique properties of practical interest. Cubosome formation can be optimized to engineer pore size or consist of bioactive lipids, polymers can be used for targeting to the outer circle and they are highly secure under physiological conditions. This type of network structure gives them greater drug trapping potential. Related to liposomes, the structure adds a significantly more enhanced membrane surface area to trap membrane proteins and small drug entities. Cubosome may increase the solubility of poorly soluble drugs. Due to modern advances, nanoparticles patterns include drug delivery, membrane bioreactors, artificial cells and biosensors and can be engineered both in vitro. This review, focused on modern advances in cubosome technology, not only facilitates their work but also contributes to standard procedures for the rational design of innovative systems for biomedical applications. Due to the nature of cubosome dispersion being bio-adhesive and biocompatible, as well as having different properties, cubosomes are functional systems, administered in a variety of ways, such as orally and parenterally. Cubosome structure is investigated through electron microscopy, light scattering, X-rays, and NMR, although some researchers are studying the potential of cubosomes as a delivery system.